Waste Management Crisis at the Terjun Medan Landfill: Analysis of Local Government Legal Responsibility - Simanungkalit, Angelica; Rosmalinda; Affila (Universitas PGRI Madiun, 2026)
Medan City is facing a serious environmental crisis due to a nearly 50-meter-high pile of waste at the Terjun Final Disposal Site (TPA Terjun), which is managed using an open dumping system. This condition indicates a failure in local government governance to fulfill waste management obligations as stipulated in Law Number 18 of 2008 concerning Waste Management and Law Number 32 of 2009 concerning Environmental Protection and Management. This failure has resulted in violations of the public’s right to a healthy environment as guaranteed by the 1945 Constitution. Negative impacts such as groundwater contamination, air pollution, and health risks threatening the surrounding residents constitute environmental injustice. Local governments may face administrative sanctions and lawsuits for compensation and have an obligation to carry out environmental restoration. Addressing this crisis requires active roles from the Medan City Government, central and provincial governments, the public to realize effective, sustainable, and environmentally friendly waste management